Cell division cycle 23 is required for mouse oocyte meiotic maturation - Zhou, Qian; Li, Jian; Yue, Wei; Li, Ang; Meng, Tie-Gang; Lei, Wen-Long; Fan, Li-Hua; Ouyang, Ying-Chun; Schatten, Heide; Wang, Zhen-Bo; Sun, Qing-Yuan (The FASEB journal, 2020)
Precise regulation of chromosome segregation during oocyte meiosis is of vital importance to mammalian reproduction. Anaphase promoting complex/cyclosome (APC/C) is reported to play an important role in metaphase-to-anaphase transition. Here we report that cell division cycle 23 (Cdc23, also known as APC8) plays a critical role in regulating the oocyte chromosome separation. Cdc23 localized on the meiotic spindle, and microinjection of Cdc23 siRNA caused decreased ratios of metaphase-to-anaphase transition. Loss of Cdc23 resulted in abnormal spindles, misaligned chromosomes, errors of homologous chromosome segregation, and production of aneuploid oocytes. Further study showed that inactivation of spindle assembly checkpoint and degradation of Cyclin B1 and securin were disturbed after Cdc23 knockdown. Furthermore, we found that inhibiting spindle assembly checkpoint protein Msp1 partly rescued the decreased polar body extrusion and reduced the accumulation of securin in Cdc23 knockdown oocytes. Taken together, our data demonstrate that Cdc23 is required for the chromosome segregation through regulating the spindle assembly checkpoint activity, and cyclin B1 and securin degradation in meiotic mouse oocytes.